2018
DOI: 10.1021/acs.chemmater.7b04201
|View full text |Cite
|
Sign up to set email alerts
|

High-Loading Intermetallic Pt3Co/C Core–Shell Nanoparticles as Enhanced Activity Electrocatalysts toward the Oxygen Reduction Reaction (ORR)

Abstract: A facile, seed-mediated growth method and postannealing treatment have been employed to synthesize a single-phase 40% mass loading intermetallic Pt 3 Co/Vulcan electrocatalyst, enabling the electrocatalytic layer to be thinner and thus lowering the mass transport resistance for the ORR in proton exchange membrane fuel cells (PEMFCs). These 40% Pt 3 Co/C nanocatalysts exhibited superior kinetics toward the ORR, relative to a 20% Pt 3 Co/C catalyst, and only showed a slight degradation in the half-wave potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 44 publications
1
107
0
Order By: Relevance
“…The ECSA of the Au@PtCoAu/C catalyst was higher than that of the Pt 4 Co/C, indicating a better Pt utilization in the Au@PtCoAu/C catalysts. [ 33–34 ] It could be also observed that the ECSA of the Au@Co@PtCoAu/C catalyst was relatively smaller than the Au@PtCoAu/C catalyst. In previous reports, the segregation of Au to the surface layer was used to explain the decreased ECSA for some samples with Au cores.…”
Section: Resultsmentioning
confidence: 99%
“…The ECSA of the Au@PtCoAu/C catalyst was higher than that of the Pt 4 Co/C, indicating a better Pt utilization in the Au@PtCoAu/C catalysts. [ 33–34 ] It could be also observed that the ECSA of the Au@Co@PtCoAu/C catalyst was relatively smaller than the Au@PtCoAu/C catalyst. In previous reports, the segregation of Au to the surface layer was used to explain the decreased ECSA for some samples with Au cores.…”
Section: Resultsmentioning
confidence: 99%
“…The strategies to minimize the Pt amount call for a shift from monometallic nanoparticles (NPs) to the use of nano-engineered architectures with tailored morphologies and compositions [ 1 , 2 ]. For instance, bi- or tri-metallic particles, alloys [ 3 , 4 , 5 , 6 ] and successively de-alloyed [ 7 ] structures where Pt is associated with other transition metals (e.g., Ni, Co, Cu) have been prepared and demonstrated high ORR activity and durability. Another very promising class of tailored electrocatalysts is represented by core@shell nanostructures with a thin Pt skin covering a transition metal core in 0D (particle-like) [ 8 , 9 , 10 ] and 1D (fiber-like) morphologies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 [351,352]. And through surface segregation, numerous core-shell-structured electrocatalysts, such as Pd@Pt, Ru@Pt, Au@Pt, Cu@Pt, Fe@ Pt, Co@Pt, and Ni@Pt have been synthesized [353][354][355][356][357][358][359].…”
Section: Principles and Development Of Surface Segregationmentioning
confidence: 99%